Techniques Of Translating English Figurative Expressions In ‘Colours’ Magazine By Garuda Indonesia Into Indonesian - Ni Luh Putu Unix Sumartini (RETORIKA: Jurnal Ilmu Bahasa, 2016)
The article is aimed to find out the Techniques of Translating English Figurative Expression in ‘Colours’ Magazine by Garuda Indonesia into Indonesian. There are three problems are discussed in this study, namely (1) types of figurative expressions found in the English version of ‘Colours’ magazine and their translation’s equivalence into Indonesian and (2) kinds of translation techniques applied in translating the English figurative expression into Indonesian, This research belongs to qualitative research and the data used in this study were taken from the ‘Colours’ magazine by Garuda Indonesia. The main theory which is applied in this study is taken from the theory of Molina & Albir (2002) in their book entitled Translation Techniques Revisited; A Dynamic and Functionalist Approach. Another theory applied is taken from the theory of McArthur (1992) in his book entitled The Oxford Companion on The English Language. Other supporting theories which are used to support this study are the theory of Larson (1998) in her book entitled Meaning-Based Translation and some other books considered relevant to the topic. The result showed that there are eleven kinds of English figurative expressions found in the data. They are antithesis, euphemism, hyperbole, idioms, irony, metaphor, metonimy, personification, pleonasm, simile and synecdoche. In translating techniques, the translator applied ten translating techniques, they are; adaptation, borrowing, compensation, description, established equivalent, linguistic comprehension, literal technique, modulation, reduction and transposition. In translating a figurative expression from SL into TL, some of the results showed that an English figurative expression is translated into Indonesian figurative translation but some of them can not maintain its figurativeness in Indonesian, therefore the English figurative expression is translated into Indonesian non-figuratively. Keywords: Techniques of Translating, English Figurative Expression, Colours Magazin